Early GSWC Clippings 1932 - (:unkn) unknown (My University, 1932)
The girls at the college kept busy during this time. They participated in many campus events such as the May Day Festival and other performances. They had many entries to the Pine Branch (the campus's literary magazine at the time), many club interactions, and lots of Alumni activities.
Early Georgia State Women's College (G.S.W.C). " Early GSWC Clippings 1932," 1912-2000. 1 electronic record. 1 pdf document.
Keywords: Clippings (Books, Newspapers, etc.); Georgia State Woman's College; Newspapers